Comparing Healthcare Resource Utilization and Costs for Patients with Normal Tension Glaucoma Across Levels of Severity: A Retrospective Cohort Study - Beal B (Dove Medical Press, 2021)
Brennan Beal,1 Vanessa Shih,2 Joanna Campbell,2 David Veenstra,1 Beth Devine1 1The Comparative Health Outcomes, Policy and Economics (CHOICE) Institute, University of Washington, Seattle, WA, USA; 2Healthcare Economics and Outcomes Research, AbbVie, Chicago, IL, USACorrespondence: Brennan BealThe Comparative Health Outcomes, Policy and Economics (CHOICE) Institute, University of Washington, Suite H-375, Box 35760, 1959 NE Pacific Street, Seattle, WA, 98195-7630, USATel +1 704 742 0288Fax +1 206-543-3835Email brennanbeal@gmail.comPurpose: To estimate the healthcare resource utilization (HCRU) and costs for patients with normal tension glaucoma (NTG) as well as their payers across various levels of disease severity.Patients and Methods: Our study was a retrospective cohort study of 6330 US NTG patients. Patients were enrolled if they were 40 years or older and had two or more qualifying NTG diagnoses within the enrollment period, October 1st, 2015 to December 31st, 2017. Our analysis was carried out for two cohorts – those with unilateral disease and those with bilateral disease. Baseline demographic and clinical characteristics were assessed for a 12-month pre-index period. The follow up period was 12-months post-index. We employed generalized linear models to model HCRU and costs.Results: Patients with severe, bilateral disease, filled more than two additional prescriptions annually (2.5, p< 0.001, 95% CI [2.0, 3.1]) when compared to their mild counterparts and accounted for 111 (p< 0.001, 95% CI [83.5, 139.1]) extra days of supply of glaucoma medications. These patients face an adjusted $187 (p< 0.001, 95% CI [145, 229]) more out-of-pocket (OOP), and payers an additional $598 (p< 0.001, 95% CI [$370, $826]), than their counterparts with a mild diagnosis on an annual basis. Total annual payer costs, on average (SD) for those with severe bilateral NTG were $1175 ($2222).Conclusion: Our results suggest that patient and payer burden is significantly greater for those with severe disease compared to those with mild NTG. The excess burden is attributed to additional HCRU and the associated financial burden. Payers experienced a much larger financial burden from patients with severe disease compared to those with mild NTG. Approximately half of the cost differences can be attributed to additional prescription use.Keywords: healthcare resource utilization, normal tension glaucoma, low tension glaucoma, healthcare costs